Characterizing Fish–Habitat Associations through Paired Fisheries‐Independent and In Situ Habitat Assessments. (31st January 2021) - Clarkson, Emma; Beseres Pollack, Jennifer
Abstract: Estuarine habitat has a significant influence on the growth, recruitment, and survival of fish and invertebrate species, and understanding habitat dynamics can improve fisheries management. However, the cost and effort associated with habitat monitoring can be limiting, and many large‐scale fisheries‐independent monitoring programs do not capture habitat and biological data concurrently. Consequently, fisheries and their associated habitats are often managed separately. We designed a pilot study to assess the utility and effectiveness of incorporating rapid in situ habitat characterization into a statewide fisheries management program. The occurrence of six focal species (Red Drum Sciaenops ocellatus, Spotted Seatrout Cynoscion nebulosus, blue crab Callinectes sapidus, Atlantic Croaker Micropogonias undulatus, brown shrimp Farfantepenaeus aztecus, and white shrimp Litopenaeus setiferus ) and the overall faunal community composition were compared across estuarine habitats to assess the ability of this method to accurately depict fish–habitat associations. Focal species' occurrence and community composition was significantly correlated with shoreline vegetation, seagrass presence, presence of mangroves, substrate type, and heterogeneity in vegetated habitat. This study demonstrates an effective approach to integrating habitat into fisheries‐independent monitoring in pursuit of an ecosystem‐based approach to fisheries management.